Consistency of some tomato paste (Lycopersicum esculentum Miller) from the Piura market - SÁNCHEZ CHERO, Manuel Jesús (2019)
The consumer demand for quality food fresh features has arithmetically developed. The preferences change to fresh, healthy, rich in aroma and good taste, to ready-to-eat foods with a longer shelf life. The tomato is one of the most important fruit. It is marketed primarily as processed products, i.e., pastes, concentrates, ketchup, tomato sauce and so on. The objective of this research was to calculate the consistency of four tomato pastas (Lycopersicum esculentum Miller) market of Piura and to determine the correlation between the assessments made with Bostwick consistometer and sensory evaluations. The Bostwick consistometer is used to determine the consistency of the tomato paste by determining the extent flows tomato paste down with its own weight along a flat surface centimeters scale, in 30 s per sample in descending order, Tottus: 12.4, Walibi: 8.4, “B and D”: 5.1 and Molitalia: 4.6. The correlation was inversely between the values of consistometer Bostwick and sensory scores consistency of tomato paste, with a determination coefficient of 80.85%.   Key words: Rheology, consistency, Bostwick consistometer, paste, tomato.